2020
DOI: 10.1177/0963662520917339
|View full text |Cite
|
Sign up to set email alerts
|

The ideological divide in public perceptions of self-driving cars

Abstract: Applications in artificial intelligence such as self-driving cars may profoundly transform our society, yet emerging technologies are frequently faced with suspicion or even hostility. Meanwhile, public opinions about scientific issues are increasingly polarized along the ideological line. By analyzing a nationally representative panel in the United States, we reveal an emerging ideological divide in public reactions to self-driving cars. Compared with liberals and Democrats, conservatives and Republicans expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…To measure public perceptions of AI about perceived benefits, risks, and trust, we developed constructs by following the lead of the academic literature on AI, public perceptions, and government decision automation (e.g. Fraszczyk and Mulley 2017 ; Araujo et al 2020 ; Peng 2020 ; Stai et al 2020 ; Cui and Wu 2021 ; Dennis et al 2021 ; Kassens-Noor et al 2021 ; Selwyn and Gallo Cordoba 2021 ). All items were measured on a 7-point Likert scale ranging from “disagree” to “agree” for perceived benefits and risks, and “distrust” to “trust” for the trust construct.…”
Section: Methodsmentioning
confidence: 99%
“…To measure public perceptions of AI about perceived benefits, risks, and trust, we developed constructs by following the lead of the academic literature on AI, public perceptions, and government decision automation (e.g. Fraszczyk and Mulley 2017 ; Araujo et al 2020 ; Peng 2020 ; Stai et al 2020 ; Cui and Wu 2021 ; Dennis et al 2021 ; Kassens-Noor et al 2021 ; Selwyn and Gallo Cordoba 2021 ). All items were measured on a 7-point Likert scale ranging from “disagree” to “agree” for perceived benefits and risks, and “distrust” to “trust” for the trust construct.…”
Section: Methodsmentioning
confidence: 99%
“…A parallel between fully autonomous versus semiautonomous approaches has been seen in the automobile industry over the past several decades. Companies such as Google and Tesla have made significant strides in the development of fully autonomous cars (25)(26)(27)(28), but due to the significant technical and ethical requirements needed (29)(30)(31), fully autonomous driving is not yet commercially implemented. On the other hand, semi-autonomous driving features such as lane-assist, or initiation of braking for collision avoidance have more quietly become standard in the automotive industry over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the role of ideology on attitudes toward driverless cars found an ideological divide in public reactions to the subject. Compared to liberals, conservatives expressed more concern about autonomous vehicles and more support for regulating driverless cars (Peng, 2020).…”
Section: Political Ideology and Acceptance Of Technologymentioning
confidence: 99%